RANCANGAN APLIKASI PERHITUNGAN TUNJANGAN KINERJA PADA LINGKUNGAN KANTOR WILAYAH KEMENTERIAN HUKUM DAN HAK ASASI MANUSIA JAMBI - Mulyati , Sri; Susanto, Darex; Junial Perkasa, Andika (JURNAL AKADEMIKA, 2024)
Along with the implementation of bureaucratic reform, in order to improve the performance of civil servants in the environment of the Ministry of Law and Human Right, it is necessary to provide performace allowances outside of the monthly salary. The allowence amount is not fixed which should be based on the employees'grade and performances.Therefore, the calculation of the allowence is very essential and should be done accurately.The performance allowance indicates the effectiveness of employees working performances including their punctuality to the office.Regarding to this matter,there should be abreak through in creating applications thatwill be able to assist the employees workload in the environment of the Regional Office of the Ministry of Law and Human Rights Jambi. It is hoped that the application could help in managing data and reporting the calculation of performance allowances effectively.